Upaya Guru Sosiologi Dalam Memotivasi Belajar Peserta Didik - Syaputri Intan Muqhni Akhsan; Muhammad Syukur; Andi Sadriani (Lembaga Pengembangan Kinerja Dosen, 2023)
Lack of student learning motivation makes sociology teachers take motivational actions that must be adapted to their students. This study aims to look at the sociology efforts of teachers in motivating students' learning. This research is a qualitative descriptive research. The data were collected using observation, interview and documentation techniques. Data were analyzed using data reduction techniques, data presentation and drawing conclusions. The results of the study show that sociology teachers in student learning use problem-based learning models that have been adapted to the learning desires of students in which they want to get grades and master learning material and prohibit their friends who have not mastered learning material and interactions occur between teachers and participants. teach in the classroom.